Investigating the research landscape of chlorinated paraffins over the past ten decades - Ohoro, Chinemerem Ruth; Olisah, Chijioke; Wepener, Victor (Frontiers in Toxicology, 2025)
Chlorinated paraffins (CPs) are classified as emerging persistent organic pollutants (POPs). Due to their associated environmental and health impacts, these groups of chemicals have been a subject of interest among researchers in the past decades. Here we used a scientometric approach to understand the research landscape of CPs using literature published in the Web of Science and Scopus database. RStudio and VOSviewer programs were employed as scientometric tools to analyze the publication trends in global CP-related research from 1916 to 2024. A total of 1,452 articles were published over this period, with a publication/author and co-author/publication ratio of 0.43 and 5.49, respectively. China ranked first in publication output (n = 556, 43.3%), and the highest total citations (n = 12,007), followed by Sweden (n = 90), Canada (n = 77), and Germany (n = 75). Publications from developing countries were limited, with most contributions from Africa originating from Egypt (n = 7), South Africa (n = 5), and Nigeria (n = 3), primarily through international collaborations. The average annual growth rate of 4.3% suggests a significant future article output. This scientometric analysis allowed us to infer global trends in CPs, identify tendencies and gaps, and contribute to future research. Despite having similar toxicity to short-chain chlorinated paraffin (SCCP), long-chain chlorinated paraffin (LCCP) has received less attention. Therefore, future research should prioritize studying LCCP bioaccumulation and toxicity in diverse food webs, focusing on aquatic species vulnerable to CPs and effective toxicological models. Additionally, collaborative research with developing countries should be encouraged to enhance meeting the Stockholm Convention’s demand.